THE EMPOWERMENT OF ISLAMIC COOPERATION IN POVERTY REDUCTION IN INDONESIA - Siti Nur Azizah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, Indonesia, 2016)
Talking about poverty is never-ending, because poverty did not go to the completion of the skinning community. Poverty is a disease that bite people thinking of the community in terms of power, way of life and will even be a bottomless do anything to get out of poverty. Indonesian as a country that has a community with a strong national identity, it should not come to fall to the things that will bring in contemplation. The government must be intervene in maintaining national identity since eroded grinding poverty, economic transactions are increasingly siding with the bourgeoisie. Through empowerment Islamic patterns for the general public seems to be a necessity. Through cooperatives as one of the institutions that are rooted in the community seem to be easily absorbed by the public. Especially in the era of globalization that has sunk this nation's economic order to make the national identity civilized taawun society and work together in achieving a common goal; social welfare is a right for the people of this nation become faded.